2016
DOI: 10.1038/srep28659
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Isomerization and Topochemical Polymerization of the Programmed Asymmetric Amphiphiles

Abstract: For the advancement in multi-stimuli responsive optical devices, we report the elaborate molecular engineering of the dual photo-functionalized amphiphile (abbreviated as AZ1DA) containing both a photo-isomerizable azobenzene and a photo-polymerizable diacetylene. To achieve the efficient photochemical reactions in thin solid films, the self-assembly of AZ1DA molecules into the ordered phases should be precisely controlled and efficiently utilized. First, the remote-controllable light shutter is successfully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…From careful analysis, it is found that AZ 3 P denpol in the highly ordered LC phase maintains a layered hierarchical superstructure containing the smectic F (SmF)‐like lateral azobenzene packing with 2D dimensions of a = 0.77 nm and b = 0.55 nm. The layer thickness reduced slightly to L = 5.96 nm due to the higher molecular tilt and the close molecular packing . The phase assignments and molecular packing models of AZ 3 P are illustrated in Figure b.…”
Section: Resultsmentioning
confidence: 98%
“…From careful analysis, it is found that AZ 3 P denpol in the highly ordered LC phase maintains a layered hierarchical superstructure containing the smectic F (SmF)‐like lateral azobenzene packing with 2D dimensions of a = 0.77 nm and b = 0.55 nm. The layer thickness reduced slightly to L = 5.96 nm due to the higher molecular tilt and the close molecular packing . The phase assignments and molecular packing models of AZ 3 P are illustrated in Figure b.…”
Section: Resultsmentioning
confidence: 98%
“…By combining the properties of azobenzenes and PDAs, it has been possible to design azobenzene-containing PDA systems 5462 and some of these systems displayed photo-induced colorimetric changes 61,62 . We also reported that an azobenzene-containing diacetylene monomer forms a crystalline, blue-colored PDA upon irradiation with 254 nm light 62 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this chemical change does not make notable variation in molecular packing structure (Figure S15, Supporting Information). [39,40] As a result, topochemically polymerized DACSM (Poly-DACSM) has almost identical molecular packing structure with SA-DACSM and exhibits a blue color and an extremely quenched emission due to the absorption of polydiacetylene at 𝜆 max = 628 nm and Förster resonance energy transfer (FRET) effect from cyanostilbene to polydiacetylene, respectively. [41][42][43] Additionally, Poly-DACSM exhibits a thermochromic behavior due to the presence of polydiacetylene.…”
Section: Topochemically Polymerized Dacsm and Its Changes By Thermal ...mentioning
confidence: 99%